Kesadaran Tersamar Komunitas dalam Pembangunan Kawasan Ekonomi Khusus (KEK) Singhasari di Tengah Pandemi COVID-19 - Lutfi Amiruddin; Genta Mahardhika Rozalinna; Primadiana Yunita (Society, 2021)
The development process of the Singhasari Special Economic Zone (SEZ) in heritage tourism has not paid attention to socialization to residents. On the other hand, the COVID-19 pandemic has also affected its development. With this situation, this research aims to identify the community’s readiness of cultural activists and tourism actors in the Singhasari Special Economic Zone (SEZ). Through the concept of community readiness by searching and analyzing qualitative data, this research finds two important things; first, the community of cultural and tourism activists is still in the readiness level of vague awareness. This model of awareness stems from the distribution of unclear information. The research findings suggest that these communities only get information from gossip among themselves. Second, the COVID-19 pandemic, which slows down the development process, is interpreted as a punishment from God for the SEZ organizers. This interpretation relates to the lack of disclosure of public information regarding the SEZ development process. These two results show that there are symptoms of a crisis in developing sustainable tourism industry.